Cannabidiol for epilepsy: a new indication for an old drug. (27th September 2018) - Hagopian, Samantha J; Marsh, Eric D
Medicinal cannabis,  and cannabidiol in particular, has garnered much attention in the media and medical community as a possible therapeutic for multiple conditions including epilepsy. Although the use of cannabis has been reported for centuries, evidence in its usefulness in the treatment of epilepsy has been mainly anecdotal. This review discusses emerging research on cannabidiol in the treatment of severe pediatric epilepsies, including Dravet syndrome and Lennox Gastaut syndrome. We discuss the data from both open-label and Phase III trials and report a consistently significant reduction in seizures but also concomitant drug interactions and adverse effects. Future directions of research are considered to determine the full therapeutic potential of this old, but new, class of compounds.